Jesus Loves Japan: Return Migration and Global Pentecostalism in a Brazilian Diaspora - Ikeuchi, Suma (Stanford University Press, 2019)
Cover -- Contents -- List of Illustrations -- Acknowledgments -- Prologue: Along the Big Question Mark -- PART I: BEGINNINGS -- 1 Pilgrims in the Strange Homeland -- 2 Japanese Blood, Brazilian Birth, and Transnational God -- PART II: SUSPENDED -- 3 Putting Aside Living -- 4 Neither Here nor There -- PART III: RENEWED -- 5 Back to the Present -- 6 The Culture of Love -- PART IV: CONTESTED -- 7 Of Two Bloods -- 8 Ancestors of God -- PART V: RETURNS -- 9 Accompanied Self -- 10 Jesus Loves Japan -- Epilogue: En Route to Impossible Homes -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Z.